Penyuluhan Pemasaran Dan Pengenalan Produk Pada Kerupuk Beras Oryzativa Di Desa Balung Kecamatan Arosbaya Kabupaten Bangkalan - Arisinta, Octaviana; Samsul, Faichatul Jannah (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Balung is a village located in the Arosbaya District, Bangkalan Regency, East Java Province, Indonesia. Our KKN was placed in Balung Village according to the grouping by UPPM STKIP PGRI Bangkalan. Education on rice product labels, entrepreneurship counseling, Balung oryzativa chips which are economic programs. For natural potential in Balung village, the majority of the population work as farmers. Because of its vast geographical area with rice fields. The output that we will produce is the Oryzativa Balung product, which is chips made from rice.